Comportamiento a la corrosión de varillas ½” grado 60 mediante ensayos acelerados de cámara de niebla salina (2020)
In this paper was studied the behavior, regarding to the corrosion, in this case ½” grade 60 rebars were used. Prior this, the chemical composition of the rebars was studied, founding carbon, manganese and copper as the most predominant elements. An accelerated test in a salt spray chamber was realized, where the rebars were exposed for periods of 1, 3 and 7 days, the test was performed according to ASTM B-117:2019 standard. Afterward the corrosion rate of the rebars according to ISO 9226:2012 standard was estimated and the corrosion rate-time curve was made, noticing a high corrosion rate the first day which decreased with the course of the test .Also characterization test were performed, a tensile test was carried out in the universal testing machine then with the results, stress-strain graphic was realized, later an optical microscopy test was made and the inner structure of the rebar was analyzed observing a ferrite and perlite microstructure in the transverse and longitudinal cuts, besides an X-ray diffraction (XDR) test was carried out with which an X-ray diffractogram was made and the characteristic peaks of the corrosion products found were analyzed, in such peaks were found lepidocrocite in 2θ de 15.12° y 2θ es 46.15, also in 2θ de 35.25° akageneite was found. Also, the scanning electron microscopy was performed with which the products morphology was observed, it was possible to see granular, globular and laminar formations of lepidocrocite, as well tubular formations corresponding to akageneite were found. It was concluded that the corrosion rate had high values the first days which decreased when the rebars get more mass, such values indicated that the corrosion was increasing with the course if the days, but in a lower rate. An orange coloration typical of the lepidocrocite presence in high chloride environments was found. Also, corrosion products corresponding to high chloride environments or simulated environments such the case of akageneite was found.